1997
DOI: 10.1038/sj.onc.1201305
|View full text |Cite
|
Sign up to set email alerts
|

CBFβ-SMMHC, expressed in M4Eo AML, reduced CBF DNA-binding and inhibited the G1 to S cell cycle transition at the restriction point in myeloid and lymphoid cells

Abstract: CBFb-SMMHC is expressed from the inv(16) chromosome in M4Eo AML. Mice lacking CBF subunits or expressing the CBFb-SMMHC or AML1-ETO oncoproteins failed to develop de®nitive hematopoiesis. To investigate these e ects on hematopoiesis, we expressed CBFb-SMMHC from the metallothionein promoter, in both 32D cl3 myeloid cells and Ba/F3 B-lymphoid cells. Addition of zinc increased CBFb-SMMHC levels more than tenfold, with higher levels evident in Ba/F3 lines. Levels obtained in 32D cl3 cells were similar to those of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
107
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(110 citation statements)
references
References 29 publications
3
107
0
Order By: Relevance
“…Stable transfectants were selected by limiting dilution in 96-well dishes in the presence of 1.2 mg/ml G418 (total). Zinc chloride was employed at 100 mM, and cell cycle analysis was carried out as described by pulsing for 30 min with bromodeoxyuracil (BrdU) followed by fixation and fluorescein isothiocyanateanti-BrdU and propidium iodide staining as described (Cao et al, 1997).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stable transfectants were selected by limiting dilution in 96-well dishes in the presence of 1.2 mg/ml G418 (total). Zinc chloride was employed at 100 mM, and cell cycle analysis was carried out as described by pulsing for 30 min with bromodeoxyuracil (BrdU) followed by fixation and fluorescein isothiocyanateanti-BrdU and propidium iodide staining as described (Cao et al, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Cytoplasmic proteins were concentrated by precipitation using four volumes of acetone at À201C. Nuclear and cytoplasmic extract corresponding to equivalent numbers of cells were subjected to Western blotting using rabbit anti-CBFb antiserum as described (Cao et al, 1997). Band intensities were quantified using NIH ImageJ 1.33 software.…”
Section: Cell Nucleus and Cytoplasm Isolation And Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…A carboxy-terminal portion of the chimera contains the rod domain of the myosin heavy chain molecule which is responsible for the molecule's oligomerization (Kiehart, 1990). An aminoterminal portion of the chimera harbors most of the amino acid sequence of the PEBP2b/CBFb protein, and the chimeric polypeptide itself has been shown to retain the ability to interact with the a subunit of PEBP2/CBF (Cao et al, 1997;Liu et al, 1994Liu et al, , 1996. It is also reported that the chimeric protein can deregulate PEBP2/CBF site dependent transcriptional activation in transient expression assays .…”
Section: Introductionmentioning
confidence: 99%
“…As for the PEBP2b/CBFb-SMMHC chimeric protein, its subcellular localization appears to be either cytoplasmic and/or nuclear, depending on the experimental conditions employed in each report (Cao et al, 1997;Liu et al, 1996;Lu et al, 1995;Wijmenga et al, 1996). In order to extend our previous observations on the cytoskeleton-a nity of the PEBP2b/CBFb protein , we have focused one part of the present study on the possible e ects of the cytoplasmic PEBP2b/CBFb-SMMHC protein on cell morphology and F-actin containing stress ®bers.…”
Section: Introductionmentioning
confidence: 99%